The pragmatic aspect of the reasoning texts in the 17 th. century English literature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The reference to the analysis of the texts of the XVII th. century is not accidental. This period was defined by researchers as “experimental” in the development of modern English prose. The variety of later developed verbal forms of prose was most vigorously pioneered precisely in this century. The text of reasoning is considered as a whole-formed, structural and communicative unity created on the basic of the compositional – speech form, the elements of which reproduce the speech process as the process of the work of consciousness. The revival of the rhetoric in the XVII century also determined the special nature of the generation of text in which lexico-semantic and synthetic levels were subjected to compulsory organization. The element of consciousness and correctness is obvious here, so the structure appears naked. The reasoning here is not contaminated with other compositional speech forms, but represents the whole speech production. The basis for the proposed classification of English prose texts of the XVII century in not genre-based features, but a type of compositional-speech form. The typological features of the speech structure of text-reasoning are studied. In addition to linguistic analysis of previously unexplored material, the pragmatic genre parameters of reasoning texts as a form of individual linguistic expression of thought are brought to the forefront of study. This type of text, being a linguistic expression of thinking process, has specific grammatical and syntactic features that are peculiar to it and constituting factors that depend not only on logic but also on stylistics and pragmatics helps to understand the structure of the text and the nature of compositional-style decisions. The study of the pragmatic aspect of 17 th. Century reasoning texts directly related to rhetoric allows not only to approach the disclosure of the specifics of the text model, but to study the functions of the language in certain areas of communication. Reasoning allow the writer to express his attitude to persons and events, helps to realize the pragmatic attitude of the work, to influence the reader by deliberately emphasizing the importance of an event. The process of reasoning is impossible without taking into account pragmatic factors their unity forms the essence of reasoning as a speech-thought process. The whole structure of reasoning is directly dependent on the pragmatic attitude: the nature of argumentation, evidence, analogy, and the entire system of expressive-stylistic devices and their dynamic interaction.
Keywords: composition; typology; essays; pragmatic; reasoning